Forensic Analysis of Marijuana: Approaches to Establishing Belonging to Previously Separated Plant Mass - A. N. Khokh; P. S. Voskanyan; A. A. Petrosyan (Теория и практика судебной экспертизы)
The article presents the results of the studies of dried and crushed marijuana using nearinfrared spectroscopy and spore-pollen analysis for solving an expert task of establishing the affiliation to previously separated plant masses. The recording of near-infrared spectra of expert samples has been carried out. The possibility of interpreting spectral data using discriminant analysis of projections on latent structures is shown. The taxonomic composition of 8 435 pollen grains and spores has been determined, as well as the quantitative content of each taxon. According to the results of the conducted research, it was concluded that the application of a complex of independent and complementary methods allows to obtain the necessary and sufficient number of matching signs that can be recognized as unique for identification. The proposed research scheme can be also applied to other narcotics of plant origin.